Non Perbedaan Rasio Trigliserida/High Density Lipoprotein Cholesterol (TG/HDL-C) pada Balita Stunting dan Non - Stunting di Kecamatan Gunung Sugih Kabupaten Lampung Tengah - Ulfiah Fairuz Zhafirah (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2021)
ABSTRACT Background; Stunting is the impaired growth and development that children experience from poor nutrition, repeated infection, and inadequate psychosocial stimulation. Childhood stunting has been reported to increase the risk of metabolic syndrom later in life such as obesity, insulin resistance,cardiometabolic disease, diabetes mellitus, and cardiovascular disease. It can be measured using TriGlycerides (TG) to High-Density Lipoprotein Cholesterol (HDL-C) (TG/HDL-C) ratio method. Methods: The design of this study is comparative analytic with cross sectional approach to 26 stunting and 26 non-stunting children aged from 2 – 5 years. The data taken is primary data of blood test result including TG and HDL-C. Results: Mean of TG/HDL-C ratio in Stunting children (3,8) is higher compared to non-stunting children (1,94). The independent T-test results for the TG/HDL-C ratio differences between the two groups are 0,000 (p>0,005) Conclusion: There is significant difference between TG/HDL-C ratio in stunting and non-stunting children.